Peran Teknologi Blockchain dalam Meningkatkan Transparansi dan Akuntabilitas Pengelolaan Zakat - Fajri Mulia Ningsih; Safrina Muarrifah; Rini Meliana; Amanah Aida Qur’an; Azka Nur Diana (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Zakat management is an important aspect in ensuring the effective and fair distribution of zakat funds. However, issues of transparency and accountability are often a concern in zakat management, which can reduce public trust in zakat management institutions. Blockchain technology has emerged as a promosing alternative that can bring about major change in the endeavpr to promote openness and accountability. This article discusses the role of blockchain technology in increasing public trust in zakat management by creating a decentralized, transparent and trustworthy system. Results of this research Emphasis on the absence of challenges and strategic recommendations in managing zakat with blockchain. In this case, the role of amil zakat and muzakki is key in implementation zakat uses blockchain technology in managing quality, efficient, zakat accountable and professional in distributing zakat to 8 asnaf